Applicability of mechanical tests for biomass pellet characterisation for bioenergy applications - Williams, Orla; Taylor, Simon; Lester, Edward; Kingman, Sam; Giddings, Donald; Eastwick, Carol (MDPI, 2018)
In this paper, the applicability of mechanical tests for biomass pellet characterisation was investigated. Pellet durability, quasi-static (low strain rate), and dynamic (high strain rate) mechanical tests were applied to mixed wood, eucalyptus, sunflower, miscanthus, and steam exploded and microwaved pellets, and compared to their Hardgrove Grindability Index (HGI), and milling energies for knife and ring-roller mills. The dynamic mechanical response of biomass pellets was obtained using a novel application of the Split Hopkinson pressure bar. Similar mechanical properties were obtained for all pellets, apart from steam-exploded pellets, which were significantly higher. The quasi-static rigidity (Young’s modulus) was highest in the axial orientation and lowest in flexure. The dynamic mechanical strength and rigidity were highest in the diametral orientation. Pellet strength was found to be greater at high strain rates. The diametral Young’s Modulus was virtually identical at low and high strain rates for eucalyptus, mixed wood, sunflower, and microwave pellets, while the axial Young’s Modulus was lower at high strain rates. Correlations were derived between the milling energy in knife and ring roller mills for pellet durability, and quasi-static and dynamic pellet strength. Pellet durability and diametral quasi-static strain was correlated with HGI. In summary, pellet durability and mechanical tests at low and high strain rates can provide an indication of how a pellet will break down in a mill.